The Urgence of Reconstruction the Offense of Adultery in Indonesia: A Form of Protection Against Legal Marriage and Sexual Morals Muslim Society - Any Ismayawati (Ijtimā`iyya: Journal of Muslim Society Research, 2017)
The aim of this study is to find exact formulation of the offense of adultery. Problems in the research: 1) how Indonesian muslim society understand and act toward adultery, 2) why muslimsociety solve adultery without taking 284 Criminal Code, 3) why reconstruction of adultery law is needed, The research designs are qualitative tradition, constructivism paradigm, socio legal methodology, while its approaches are hermeneutics, philosophy and phenomenological approach. Its analyzing data technique are inductive analysis through data reduction and triangulation.The results show that Indonesian muslimsociety in sanctioning toward people committing intercourse without any legal marriage. In sanctioning is based on local custom and Islamreligion believed by major local community, with its priority on justification principle, between human as individual and as social creatures, and its justification between the victim’s need and the actor’s importance.The conclusion is that adultery criteria based on society is every intercourse without legal marriage, in accordance of religion and state, both is done by heterogeneous gender or homogenous gender. The value on 284 Criminal Code clause does not suit on the believed value by society since it only protects marriage institution. Meanwhile, in the values of Islamreligion, ones whom are protected is not only marriage institution but also the values of sexual moral society, so muslimsociety does not use 284 Criminal Code clause to take an action toward adultery actor.In progressive law, if law has problem therefore it needs to be reconstructed, and it is not the people to be insisted in adopting toward the law, then 284 Criminal Code clause must be reconstructed, because it is not effective and cannot create proper justice for Indonesian society. In the concept of Legal Pluralism, to reconstruct the clause must based on religious law, local custom and state Law, to create perfect justice.